Algoritma Pemograman Excel 2013 Untuk Menyelesaikan Soal Matematika - Siti Nurhaliza Lubis; Yahfizham Yahfizham (International Forum of Researchers and Lecturers, 2024)
In this study using the help of microsoft Excel 2013 as a medium to solve mathematical problems more easily and practically. This study also uses a programming algorithm with the help of microsoft Exel to sort certain data that analyzes a value and comparison with sorting procedures in the work of completing the Excel 2013 application programming algorithm in solving mathematical problems. The method used in this study uses a research and Development approach. From the research that has been done, it was concluded that Microsoft Excel 2013 can be used as an application that helps in solving math problems.